The assessment of man and method toward the assembly line improvement in automotive manufacturing - Mohd Yusoof, M. Y.; Nik Mohamed, N. M. Z.; Nelfiyanti, .; Md Yasir, A. S. H. (Penerbit UMP, 2023)
This research deal with root cause analysis of using Lean Manufacturing principle for assembly line at X manufacturing automotive company in Malaysia. This research aims to improve the process and manpower allocation in the T-Model assembly line and to increase the productivity efficiency of Man and Method toward production output. Movement waste and waiting waste were subjects that were studied in this research. Data was collected through the interview process, observation, photos and calculating the current total production process time related to the assembly process. Process flow in the actual layout, process setup and simulation of the existing design using Witness Software were used to determine the section or method with the highest idle percentage or setup time. The witness Software was also used to simulate the improved layout, and the improvement then is suggested. In conclusion, the entire production process is presented, which initially offered very low productivity. With the line balancing and discrete event simulation model combination, productivity is increased from 3 units per shift initially to 6 units per shift manufactured product at the end. 40% increase in the production output. The proposed layout and practice are done, and the improvement was highlighted at an assembly line.